Digital disclosure: HIV status, mobile dating application design and legal responsibility. Issue 1 (2nd January 2021) - Giles, Cameron
ABSTRACT: Location-based mobile dating applications are often one of the richest sources of personal information readily accessible to strangers on the internet and in many cases this information now extends to a user's HIV status and the date of their most recent sexual health test. Drawing on qualitative data collected from dating application users, this article considers how these features construct sexual health in a manner which reinforces the uneven distribution of responsibility for preventing HIV transmission. Examining the current legal framework covering HIV transmission criminalisation in England and Wales, this piece aims to illustrate the importance of understanding how these applications are used in practice, if they are to be used at trial.